Development of Normal and Reduced Fat Formulas of Coconut and Gac (Momordica cochinchinensis Spreng) Aril Flavored Ice Cream - Akkarachaneeyakorn, Suthida; Sungpuak, Rawisara (Applied Science and Engineering Progress, 2017)
This research aimed to develop normal and reduced fat formulas of coconut and gac aril flavored ice cream. It was determined that the suitable formula for developing the normal of coconut and gac aril flavored ice cream based on the most acceptable to consumers and has the lowest melting rate was 34.85% gac aril juice, 45.15% coconut milk, and 20% sugar. For the development of the reduced fat formula that could reduce the highest amount of fat while giving the highest acceptance scores, the variables studied were the type of fat replacer (soy protein, maltodextrin, and soy protein mixed with maltodextrin in a ratio of 1:1) and amount of fat replacer (30, 50, and 70% of fat in ice cream). It was found that the use of soy protein mixed with maltodextrin as a fat replacer at 50% was suitable for the production of the reduced fat formula of coconut and gac aril flavored ice cream (average overall acceptance was 6.53±1.43 points). The results showed that consumers cannot distinguish the differences of the normal and reduced fat formulas of coconut and gac aril flavored ice cream. For the melting rate, the reduced fat formula ice cream had a significantly lower melting rate than the normal formula ice cream.